Structural insights into the polypharmacological activity of quercetin on serine/threonine kinases - Baby B; Antony P; Al Halabi W; Al Homedi Z; Vijayan R (Dove Medical Press, 2016)
Bincy Baby, Priya Antony, Walaa Al Halabi, Zahrah Al Homedi, Ranjit Vijayan Department of Biology, College of Science, United Arab Emirates University, Al Ain, Abu Dhabi, United Arab Emirates Abstract: Polypharmacology, the discovery or design of drug molecules that can simultaneously interact with multiple targets, is gaining interest in contemporary drug discovery. Serine/threonine kinases are attractive targets for therapeutic intervention in oncology due to their role in cellular phosphorylation and altered expression in cancer. Quercetin, a naturally occurring flavonoid, inhibits multiple cancer cell lines and is used as an anticancer drug in Phase I clinical trial. Quercetin glycosides have also received some attention due to their high bioavailability and activity against various diseases including cancer. However, these have been studied to a lesser extent. In this study, the structural basis of the multitarget inhibitory activity of quercetin and isoquercitrin, a glycoside derivative, on serine/threonine kinases using molecular modeling was explored. Structural analysis showed that both quercetin and isoquercitrin exhibited good binding energies and interacted with aspartate in the highly conserved Asp–Phe–Gly motif. The results indicate that isoquercitrin could be a more potent inhibitor of several members of the serine/threonine kinase family. In summary, the current structural evaluation highlights the multitarget inhibitory property of quercetin and its potential to be a chemical platform for oncological polypharmacology. Keywords: serine/threonine kinases, quercetin, isoquercitrin, docking, polypharmacology